Preparation method of superfine boron carbide spray granulation powder
By modifying ultrafine boron carbide and crosslinking with nitrogen silane oligomers, combining tetrabutyl titanate and spray granulation technology, ultrafine boron carbide spray granulation powder was prepared, which solved the problem of uneven distribution of ultrafine boron carbide agglomeration and toughener, and significantly improved the mechanical properties of the ceramic.
Patent Information
- Application Number
- CN202510257414.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
Ultrafine boron carbide is prone to agglomeration, and traditional toughening substances are difficult to fully contact with ultrafine boron carbide, which limits the densification and toughening effect of the ceramic body.
Ultrafine boron carbide is modified by vinyl triethoxysilane, and the cross-linking action of nitrogen silane oligomers is formed to form a boron carbide composite powder, and then ball milling and spray granulation with tetrabutyl titanate and deionized water to prepare ultrafine boron carbide spray granulation powder.
The relative density, flexural strength and fracture toughness of boron carbide ceramics have been significantly improved, with flexural strength reaching above 480 MPa and fracture toughness reaching above 6.5 MPa·m¹/².
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a method for preparing ultrafine boron carbide spray granulation powder. Background Art
[0002] Boron carbide is a ceramic material with high hardness, low density, high melting point and excellent wear resistance. It is widely used in bulletproof armor, wear-resistant parts and nuclear radiation shielding. However, the inherent brittleness and low fracture toughness of boron carbide ceramics limit their further application in high-performance structural materials. In order to improve the comprehensive properties of boron carbide ceramics, researchers usually improve their flexural strength and fracture toughness by refining the grains, introducing toughening phases or optimizing the sintering process.
[0003] Ultrafine boron carbide powder has become an ideal raw material for the preparation of high-performance boron carbide ceramics due to its high specific surface area and high activity. However, ultrafine boron carbide powder is prone to agglomeration in practical applications, resulting in poor contact between particles during sintering, and low relative density and mechanical properties of the sintered body. In addition, traditional toughening phases (such as silicon carbide, titanium carbide, etc.) are difficult to distribute evenly and fully contact with ultrafine boron carbide, further limiting the densification of the ceramic body and the toughening effect of the toughening material. Therefore, how to effectively solve the agglomeration problem of ultrafine boron carbide and achieve uniform distribution of the toughening phase is a key technical problem in the current field of boron carbide ceramic preparation. Summary of the invention
[0004] In view of this, the purpose of the present invention is to propose a method for preparing ultrafine boron carbide spray granulation powder to solve the problem that ultrafine boron carbide is easy to agglomerate, traditional toughening materials are difficult to fully contact with ultrafine boron carbide, which limits the densification of the ceramic body and the toughening effect of the toughening material.
[0005] Based on the above purpose, the present invention provides a method for preparing ultrafine boron carbide spray granulation powder, comprising the following steps: (1) Using vinyl triethoxysilane to modify ultrafine boron carbide to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice water bath, then introduce nitrogen to isolate the air, add n-hexane after 8-12 minutes, start stirring, stir for 5-20 minutes, then add methyldichlorosilane and dimethyldichlorosilane, continue stirring for 20-40 minutes, introduce ammonia, continue stirring for 4-6 hours, turn off the ammonia, continue stirring for 20-40 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under a nitrogen atmosphere, add olefin-modified ultrafine boron carbide to nitrogen silane oligomer, stir for 20-40 minutes, cross-link at high temperature, grind and sieve to obtain boron carbide composite powder; (4) Adding boron carbide composite powder and tetrabutyl titanate into deionized water, ball milling, sieving the slurry, spray granulating, and sieving the powder to obtain ultrafine boron carbide spray granulated powder.
[0006] Preferably, in step (1), the weight ratio of vinyltriethoxysilane to ultrafine boron carbide is 0.05-0.2:10.
[0007] Preferably, the mesh size of the ultrafine boron carbide in step (1) is 10000-14000 mesh.
[0008] Preferably, the amount of n-hexane added in step (2) is 8-12 times the total weight of methyldichlorosilane and dimethyldichlorosilane.
[0009] Preferably, the content of methyldichlorosilane in methyldichlorosilane and dimethyldichlorosilane in step (2) is 65wt%-75wt%.
[0010] Preferably, in step (2), the flow rate of nitrogen is 0.1-1 L / min, and the flow rate of ammonia is 0.3-0.5 L / min.
[0011] Preferably, in step (3), the weight ratio of olefinated ultrafine boron carbide to nitrogen silane oligomer is 10:0.8-1.2.
[0012] Preferably, in step (3), the high temperature crosslinking is performed by heating the temperature from room temperature to 370-380°C at a rate of 5-20°C / min and keeping the temperature for 7-9h.
[0013] Preferably, in step (4), the weight ratio of the boron carbide composite powder, tetrabutyl titanate and deionized water is 10:0.1-0.3:8-12.
[0014] Preferably, in step (4), the ball-to-material ratio of the ball milling is 4:1, the ball milling time is 20-28 h, the inlet air temperature of the spray granulation is 180-200°C, the outlet air temperature is 80-100°C, the feed pump speed is 70-90 rpm, and the vacuum degree is 0.25-0.35 KPa.
[0015] Beneficial effects of the present invention: The present invention significantly improves the comprehensive performance of boron carbide ceramics by preparing ultrafine boron carbide spray granulation powder. Compared with the ceramic body prepared by directly sintering ultrafine boron carbide, the ceramic body prepared by the spray granulation powder of the present invention has a higher relative density, a bending strength of more than 480 MPa, and a fracture toughness of more than 6.5 MPa·m¹ / ². This is mainly due to the titanium-based and silicon-based reinforcement phases generated in situ during the sintering process, which play a pinning role at the grain boundary, refine the grains and disperse the crack propagation path, thereby improving the mechanical properties of the ceramic.
[0016] The alkenyl modification of boron carbide in the present invention further improves the relative density and mechanical properties of the ceramic body. The alkenyl treatment reduces the surface energy of boron carbide, reduces the agglomeration phenomenon, and cross-links with the highly active Si-H group in the nitrogen silane oligomer, so that the nitrogen silane oligomer is evenly coated on the surface of boron carbide, fully exerting the sintering aid effect during the sintering process, thereby improving the flexural strength and fracture toughness.
[0017] The present invention adopts tetrabutyl titanate as a binder, which significantly improves the relative density, Vickers hardness, bending strength and fracture toughness of the ceramic prepared by spray granulation powder. On the one hand, tetrabutyl titanate as a binder improves the density of the green blank, and on the other hand, it provides a titanium source and a carbon source, which is helpful for in-situ generation of titanium-based and silicon-based reinforcement phases, and further enhances the comprehensive performance of the ceramic. DETAILED DESCRIPTION
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0019] In a specific embodiment of the present invention, the mesh size of the ultrafine boron carbide is 12500 meshes.
[0020] Embodiment 1:
[0021] (1) Add 0.05 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 20 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 10 min, heat to 60 ° C, stir for 5 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.1 L / min. After 12 minutes, add 8 g of n-hexane, stir for 5 minutes, then add 0.65 g of methyldichlorosilane and 0.35 g of dimethyldichlorosilane, continue stirring for 20 minutes, introduce ammonia at a flow rate of 0.3 L / min, continue stirring for 4 hours, turn off the ammonia, continue stirring for 20 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, 10 g of olefin-modified ultrafine boron carbide was added to 0.8 g of nitrogen silane oligomer, stirred for 20 min, then heated from room temperature to 370 °C at a rate of 5 °C / min, kept warm for 7 h, and ground through a 100-mesh sieve to obtain a boron carbide composite powder; (4) 10 g of boron carbide composite powder and 0.1 g of tetrabutyl titanate were added to 8 g of deionized water, and the mixture was placed in a ball mill equipped with a boron carbide ball mill for ball milling. The ball-to-material ratio was 4:1 and the ball milling time was 20 h. The ball-milled slurry was then sieved through an 80-mesh sieve and spray granulated in a centrifugal spray drying tower. The inlet air temperature was 180 °C, the outlet air temperature was 80 °C, the feed pump speed was 70 rpm, and the vacuum degree was 0.25 KPa. After spray granulation, the powder was sieved through a 40-mesh sieve to obtain ultrafine boron carbide spray granulated powder.
[0022] Embodiment 2:
[0023] (1) Add 0.1 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 30 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 20 min, heat to 60 ° C, stir for 6 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.5 L / min. After 10 minutes, add 10 g of n-hexane, stir for 10 minutes, then add 0.7 g of methyldichlorosilane and 0.3 g of dimethyldichlorosilane, continue stirring for 30 minutes, introduce ammonia at a flow rate of 0.4 L / min, continue stirring for 5 hours, turn off the ammonia, continue stirring for 30 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, add 10 g of olefin-modified ultrafine boron carbide to 1 g of nitrogen silane oligomer, stir for 30 min, then heat from room temperature to 380 °C at a rate of 10 °C / min, keep warm for 8 h, grind through a 100-mesh sieve to obtain a boron carbide composite powder; (4) Add 10 g of boron carbide composite powder and 0.2 g of tetrabutyl titanate to 10 g of deionized water, put them into a ball mill equipped with a boron carbide ball mill for ball milling, the ball-to-material ratio is 4:1, the ball milling time is 24 h, then the ball-milled slurry is sieved with an 80-mesh sieve, and then spray granulated in a centrifugal spray drying tower, the inlet air temperature is 190 ° C, the outlet air temperature is 90 ° C, the feed pump speed is 80 rpm, the vacuum degree is 0.3 KPa, and after spray granulation, the powder is sieved with a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0024] Embodiment 3:
[0025] (1) Add 0.2 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 40 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 30 min, heat to 60 ° C, stir for 7 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 1 L / min. After 8 minutes, add 12 g of n-hexane, stir for 20 minutes, then add 0.75 g of methyldichlorosilane and 0.25 g of dimethyldichlorosilane, continue stirring for 40 minutes, introduce ammonia at a flow rate of 0.5 L / min, continue stirring for 6 hours, turn off the ammonia, continue stirring for 40 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, 10 g of olefin-modified ultrafine boron carbide was added to 1.2 g of nitrogen silane oligomer, stirred for 40 min, then heated from room temperature to 390 °C at a rate of 20 °C / min, kept warm for 9 h, and ground through a 100-mesh sieve to obtain a boron carbide composite powder; (4) 10 g of boron carbide composite powder and 0.3 g of tetrabutyl titanate were added to 12 g of deionized water, and the mixture was placed in a ball mill equipped with a boron carbide ball mill for ball milling. The ball-to-material ratio was 4:1 and the ball milling time was 28 h. The ball-milled slurry was then sieved through an 80-mesh sieve and spray granulated in a centrifugal spray drying tower. The inlet air temperature was 200 °C, the outlet air temperature was 100 °C, the feed pump speed was 90 rpm, and the vacuum degree was 0.35 KPa. After spray granulation, the powder was sieved through a 40-mesh sieve to obtain ultrafine boron carbide spray granulated powder.
[0026] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the ultrafine boron carbide is not olefin-modified; The specific steps are as follows: (1) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.5 L / min. After 10 minutes, add 10 g of n-hexane, stir for 10 minutes, then add 0.7 g of methyldichlorosilane and 0.3 g of dimethyldichlorosilane, continue stirring for 30 minutes, introduce ammonia at a flow rate of 0.4 L / min, continue stirring for 5 hours, turn off the ammonia, continue stirring for 30 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (2) Under nitrogen atmosphere, add 10 g of ultrafine boron carbide to 1 g of nitrogen silane oligomer, stir for 30 min, then heat from room temperature to 380 °C at a rate of 10 °C / min, keep warm for 8 h, grind through a 100 mesh sieve to obtain a boron carbide composite powder; (3) Add 10 g of boron carbide composite powder and 0.2 g of tetrabutyl titanate to 10 g of deionized water, put them into a ball mill equipped with a boron carbide ball mill for ball milling, the ball-to-material ratio is 4:1, the ball milling time is 24 h, then the ball-milled slurry is sieved with an 80-mesh sieve, and then spray granulated in a centrifugal spray drying tower, the inlet air temperature is 190 ° C, the outlet air temperature is 90 ° C, the feed pump speed is 80 rpm, the vacuum degree is 0.3 KPa, and after spray granulation, the powder is sieved with a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0027] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the methyldichlorosilane in step (2) is replaced by dimethyldichlorosilane; The specific steps are as follows: (1) Add 0.1 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 30 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 20 min, heat to 60 ° C, stir for 6 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.5 L / min. After 10 minutes, add 10 g of n-hexane, stir for 10 minutes, then add 1 g of dimethyldichlorosilane, continue stirring for 30 minutes, introduce ammonia at a flow rate of 0.4 L / min, continue stirring for 5 hours, turn off the ammonia, continue stirring for 30 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, add 10 g of olefin-modified ultrafine boron carbide to 1 g of nitrogen silane oligomer, stir for 30 min, then heat from room temperature to 380 °C at a rate of 10 °C / min, keep warm for 8 h, grind through a 100-mesh sieve to obtain a boron carbide composite powder; (4) Add 10 g of boron carbide composite powder and 0.2 g of tetrabutyl titanate to 10 g of deionized water, put them into a ball mill equipped with a boron carbide ball mill for ball milling, the ball-to-material ratio is 4:1, the ball milling time is 24 h, then the ball-milled slurry is sieved with an 80-mesh sieve, and then spray granulated in a centrifugal spray drying tower, the inlet air temperature is 190 ° C, the outlet air temperature is 90 ° C, the feed pump speed is 80 rpm, the vacuum degree is 0.3 KPa, and after spray granulation, the powder is sieved with a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0028] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the dimethyldichlorosilane in step (2) is replaced by methyldichlorosilane; The specific steps are as follows: (1) Add 0.1 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 30 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 20 min, heat to 60 ° C, stir for 6 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.5 L / min. After 10 minutes, add 10 g of n-hexane, stir for 10 minutes, then add 1 g of methyldichlorosilane, continue stirring for 30 minutes, introduce ammonia at a flow rate of 0.4 L / min, continue stirring for 5 hours, turn off the ammonia, continue stirring for 30 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, add 10 g of olefin-modified ultrafine boron carbide to 1 g of nitrogen silane oligomer, stir for 30 min, then heat from room temperature to 380 °C at a rate of 10 °C / min, keep warm for 8 h, grind through a 100-mesh sieve to obtain a boron carbide composite powder; (4) Add 10 g of boron carbide composite powder and 0.2 g of tetrabutyl titanate to 10 g of deionized water, put them into a ball mill equipped with a boron carbide ball mill for ball milling, the ball-to-material ratio is 4:1, the ball milling time is 24 h, then the ball-milled slurry is sieved with an 80-mesh sieve, and then spray granulated in a centrifugal spray drying tower, the inlet air temperature is 190 ° C, the outlet air temperature is 90 ° C, the feed pump speed is 80 rpm, the vacuum degree is 0.3 KPa, and after spray granulation, the powder is sieved with a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0029] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that tetrabutyl titanate is not added in step (4); The specific steps are as follows: (1) Add 0.1 g of vinyl triethoxysilane to a mixed solution of 90 g of anhydrous ethanol and 30 g of deionized water, stir for 30 min, then add 10 g of ultrafine boron carbide, ultrasonicate for 20 min, heat to 60 ° C, stir for 6 h, wash with water, wash with alcohol, and dry to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice-water bath at 0°C, then introduce nitrogen to isolate the air, with an ammonia flow rate of 0.5 L / min. After 10 minutes, add 10 g of n-hexane, stir for 10 minutes, then add 0.7 g of methyldichlorosilane and 0.3 g of dimethyldichlorosilane, continue stirring for 30 minutes, introduce ammonia at a flow rate of 0.4 L / min, continue stirring for 5 hours, turn off the ammonia, continue stirring for 30 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under nitrogen atmosphere, add 10 g of olefin-modified ultrafine boron carbide to 1 g of nitrogen silane oligomer, stir for 30 min, then heat from room temperature to 380 °C at a rate of 10 °C / min, keep warm for 8 h, grind through a 100-mesh sieve to obtain a boron carbide composite powder; (4) Add 10 g of boron carbide composite powder to 10 g of deionized water, put it into a ball mill equipped with a boron carbide ball mill for ball milling, the ball-to-material ratio is 4:1, the ball milling time is 24 h, then the ball-milled slurry is sieved with an 80-mesh sieve, and then spray granulated in a centrifugal spray drying tower, the inlet air temperature is 190 ° C, the outlet air temperature is 90 ° C, the feed pump speed is 80 rpm, the vacuum degree is 0.3 KPa, and after spray granulation, the powder is sieved with a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0030] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the boron carbide composite powder in step (4) is replaced by ultrafine boron carbide; The specific steps are as follows: 10g of ultrafine boron carbide and 0.2g of polyvinyl alcohol 1788 were added to 10g of deionized water, and the mixture was put into a ball mill equipped with a boron carbide ball mill for ball milling. The ball-to-material ratio was 4:1, and the ball milling time was 24 h. The ball-milled slurry was then sieved through an 80-mesh sieve and spray granulated in a centrifugal spray drying tower. The inlet air temperature was 190°C, the outlet air temperature was 90°C, the feed pump speed was 80rpm, and the vacuum degree was 0.3KPa. After spray granulation, the powder was sieved through a 40-mesh sieve to obtain ultrafine boron carbide spray granulation powder.
[0031] Performance Test: Preparation of ceramic body: Pour the ultrafine boron carbide spray granulation powder prepared in the examples and comparative examples into a mold, and the molding pressure is 2T / cm 2 , obtain a green blank, then put the green blank into a sintering furnace, heat it from room temperature to 600°C at 5°C / min, keep it warm for 2h, then heat it from 600°C to 1500°C at 10°C / min, introduce argon protection, heat it from 1500°C to 2200°C at 10°C / min, keep it warm for 3h, and obtain a ceramic body.
[0032] Relative density: The relative density of the ceramic bodies corresponding to the embodiments and comparative examples was tested by the Archimedean drainage method. The results are shown in Table 1.
[0033] Hardness: The Vickers hardness of the ceramic bodies of the embodiments and comparative examples was tested using a microhardness tester. The results are shown in Table 1.
[0034] Bending strength: The bending strength of the ceramic bodies corresponding to the embodiments and comparative examples was tested using a double-column table-top material testing machine. The results are shown in Table 1.
[0035] Fracture toughness: The fracture toughness of the ceramic bodies corresponding to the embodiments and comparative examples was tested by the single-edge notched beam method, with a notch depth of 0.5 mm and a width of 0.2 mm. The results are shown in Table 1.
[0036] Table 1 Performance test results
[0037] Data Analysis: From the data of Examples 1-3 and Comparative Example 5 in Table 1, it can be seen that, compared with the ceramic body prepared by directly sintering ultrafine boron carbide, the ultrafine boron carbide spray granulated powder provided by the present invention has a significantly improved relative density. Although the Vickers hardness is slightly reduced, its flexural strength reaches more than 480 MPa and the fracture toughness reaches 6.5 MPa·m 1 / 2 The above is mainly due to the titanium-based and silicon-based reinforcement phases generated in situ during sintering. As the sintering temperature increases, they can play a pinning role on the boron carbide grain boundaries, hinder the movement of the boron carbide grain boundaries, effectively refine the grains, and disperse the crack propagation path. At the same time, it reduces the crack propagation energy, thereby improving the overall performance of the product.
[0038] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the olefination modification of boron carbide helps to increase the relative density of the ceramic body, overcome the problem of a significant decrease in Vickers hardness, and further improve the flexural strength and fracture toughness. This is mainly because the olefination of ultrafine boron carbide reduces the surface energy of ultrafine boron carbide, which reduces the agglomeration of ultrafine boron carbide on the one hand and improves its dispersion in nitrogen silane oligomers on the other hand. In addition, the olefination group can be cross-linked with the highly active Si-H group in the nitrogen silane oligomer, so that the nitrogen silane oligomer is evenly wrapped with the surface of the ultrafine boron carbide, and the sintering-aiding effect is fully exerted in the later sintering process.
[0039] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that when only dimethyldichlorosilane is used, the relative density of the ceramic body is low, and the flexural strength and fracture toughness are both reduced. This is mainly because the nitrogen silane oligomer formed by using only dimethyldichlorosilane lacks highly active Si-H groups, making it difficult to effectively wrap around the surface of ultrafine boron carbide through cross-linking, and in the later sintering process, a large-particle silicon-based reinforcement phase will be formed, resulting in a decrease in the contact area between the reinforcement phase and the ultrafine boron carbide, making it difficult to fully exert the sintering enhancement effect.
[0040] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that when only methyldichlorosilane is used, the Vickers hardness of the ceramic body decreases significantly. This is mainly due to the low carbon content in methyldichlorosilane and the low content of high-hardness silicon carbide and titanium carbide produced during the sintering process, thereby reducing the Vickers hardness.
[0041] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that the addition of tetrabutyl titanate effectively improves the relative density, Vickers hardness, flexural strength and fracture toughness of the ceramic. This is mainly because tetrabutyl titanate, on the one hand, acts as a binder to increase the density of the green blank, and on the other hand, provides a titanium source and a carbon source, which helps to generate titanium-based and silicon-based reinforcement phases in situ.
[0042] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing ultrafine boron carbide spray granulation powder, characterized in that: The following steps are involved: (1) Using vinyl triethoxysilane to modify ultrafine boron carbide to obtain olefinated ultrafine boron carbide; (2) Place the flask in an ice water bath, then introduce nitrogen to isolate the air, add n-hexane after 8-12 minutes, start stirring, stir for 5-20 minutes, then add methyldichlorosilane and dimethyldichlorosilane, continue stirring for 20-40 minutes, introduce ammonia, continue stirring for 4-6 hours, turn off the ammonia, continue stirring for 20-40 minutes, turn off the nitrogen, filter, and distill to obtain nitrogen silane oligomers; (3) Under a nitrogen atmosphere, add olefin-modified ultrafine boron carbide to nitrogen silane oligomer, stir for 20-40 minutes, cross-link at high temperature, grind and sieve to obtain boron carbide composite powder; (4) Adding boron carbide composite powder and tetrabutyl titanate into deionized water, ball milling, sieving the slurry, spray granulating, and sieving the powder to obtain ultrafine boron carbide spray granulated powder.
2. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (1), the weight ratio of vinyltriethoxysilane to ultrafine boron carbide is 0.05-0.2:
10.
3. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: The mesh size of the ultrafine boron carbide in step (1) is 10000-14000 mesh.
4. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (2), the amount of n-hexane added is 8-12 times the total weight of methyldichlorosilane and dimethyldichlorosilane.
5. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (2), the content of methyldichlorosilane in methyldichlorosilane and dimethyldichlorosilane is 65wt%-75wt%.
6. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In step (2), the flow rate of nitrogen is 0.1-1 L / min, and the flow rate of ammonia is 0.3-0.5 L / min.
7. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (3), the weight ratio of olefinated ultrafine boron carbide to nitrogen silane oligomer is 10:0.8-1.
2.
8. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (3), the high temperature crosslinking is performed by heating the temperature from room temperature to 370-380°C at a rate of 5-20°C / min and keeping the temperature for 7-9h.
9. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (4), the weight ratio of the boron carbide composite powder, tetrabutyl titanate and deionized water is 10:0.1-0.3:8-12.
10. The method for preparing ultrafine boron carbide spray granulation powder according to claim 1, characterized in that: In the step (4), the ball-to-material ratio of the ball milling is 4:1, the ball milling time is 20-28 h, the inlet air temperature of the spray granulation is 180-200°C, the outlet air temperature is 80-100°C, the feed pump speed is 70-90rpm, and the vacuum degree is 0.25-0.35KPa.
Citation Information
Patent Citations
Method for preparing pyroceram fibre
CN101148359A
Method for preparing carbon / carbon-silicon carbide (C / C-SiC) composite self-sealing and anti-oxidation coating
CN101905979A
Preparation method and densification process of ultrahigh-temperature multiphase ceramic powder
CN111732437A
Boron carbide / silicon carbide ceramic hollow microspheres and preparation method thereof
CN112851392A
Preparation method of high-density boron carbide ceramic
CN114538929A